2005
DOI: 10.1614/wt-04-272r.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Japanese Stiltgrass (Microstegium vimineum) to Application Timing, Rate, and Frequency of Postemergence Herbicides1

Abstract: Japanese stiltgrass is a nonnative invasive grass that occurs in a variety of habitats and is widely distributed throughout the eastern United States. In natural areas such as forests, herbicide options that selectively control Japanese stiltgrass while preserving native herbaceous and woody vegetation may be desired. The efficacy of three selective postemergence herbicides (fenoxaprop-P, imazapic, and sethoxydim) applied early season, midseason, or late season on monoculture understory stands of Japanese stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Thus, it is essential to maintain a weed-controlled environment for the crop at these initial growth stages [54], making quick weed detection a crucial tool for preventing yield losses. On the other hand, the timing of post-emergency herbicide applications impacts control efficiency [55]. Usually, the herbicide application window depends on weather conditions, weed species and crops, and can be as short as a two-to three-day window.…”
Section: Prescription Mapsmentioning
confidence: 99%
“…Thus, it is essential to maintain a weed-controlled environment for the crop at these initial growth stages [54], making quick weed detection a crucial tool for preventing yield losses. On the other hand, the timing of post-emergency herbicide applications impacts control efficiency [55]. Usually, the herbicide application window depends on weather conditions, weed species and crops, and can be as short as a two-to three-day window.…”
Section: Prescription Mapsmentioning
confidence: 99%
“…The correlation between M. vimineum growth and increased light (Claridge and Franklin 2002;Droste et al 2010;Flory 2010;Horton and Neufeld 1998;Winter et al 1982) suggests that reproduction increases with solar irradiation, and Cheplick (2010) demonstrated that seed production increased with direct sunlight and not soil moisture. Individual plants can produce 100-1,000 seeds, resulting in an estimated 0.1-4 million seeds per m 2 (Barden 1996;Cheplick 2008;Gibson et al 2002;Judge et al 2005). However, flowering and seed production vary considerably, and even fail, between years and across populations (Gibson et al 2002).…”
Section: Lightmentioning
confidence: 99%
“…Further, as an annual plant, M. vimineum relies on recruitment from a soil seed bank for persistence, and M. vimineum seeds appear to remain viable for at least three years (Barden 1987;Gibson et al 2002;Judge 2008). The persistence of a viable seed bank gives M. vimineum the ability to rebound from repeated stressors such as drought or herbicide treatment that induce mortality or reproductive failure (Gibson et al 2002;Judge 2008;Judge et al 2005;Webster et al 2008). While M. vimineum seeds can remain dormant and, in doing so, may minimize the need for annual reproduction, successful dormancy depends on seed viability.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Sethoxydim has been shown to control Japanese stiltgrass POST (Gover et al 2003;Jones et al 2004;Judge et al 2005a;Judge et al 2005b), but also controls a broader spectrum of grasses including both annual and perennial grasses (Senseman 2007). When considering how management of Japanese stiltgrass impacts desirable native vegetation such as perennial grasses, perhaps fenoxaprop-P will have fewer nontarget impacts.…”
mentioning
confidence: 99%
“…When considering how management of Japanese stiltgrass impacts desirable native vegetation such as perennial grasses, perhaps fenoxaprop-P will have fewer nontarget impacts. Fenoxaprop-P has also been shown to control Japanese stiltgrass POST (Jones et al 2004;Judge et al 2005a;Judge et al 2005b) and does not injure dicots, rushes (Juncaceae), sedges (Cyperaceae), or most perennial grasses (Poaceae) (Senseman 2007).…”
mentioning
confidence: 99%